Profesionalisme Tenaga Tata Usaha Dalam Pelaksanaan Administrasi Perkantoran - Widyastuti Aisyah Muko; Melizubaida Mahmud; Fitri Hadi Yulia Akib; Usman Moonti; Agil Bahsoan (State University of Gorontalo, 2023)
The method used in this research is a qualitative method with a descriptive approach. The results of the study show that the professionalism of the administrative staff at SMPN 16 Gorontalo City is still relatively unprofessional. Factors that support the implementation of office administration at SMP Negeri 16 Kota Gorontalo are adequate facilities and infrastructure, competencies and abilities possessed by administrative staff who are quite helpful in carrying out administration, as well as the existence of coaching or training provided by the school. Meanwhile, the factors that hamper the implementation of office administration are the educational background of administrative staff which does not lead directly to their work, the lack of administrative staff at school, as well as facilities such as damaged computers and running out of stationery. So that administrative work has not been carried out properly.